What is new in Open Access? - Swan, Alma (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
A number of quite significant developments have taken place in Open Access over the last year or so. I have already documented some of the advances in Open Access publishing and in digital repositories (Swan, 2006). In this article the focus will be upon policy developments, technological developments, new aspects of researcher behaviour, and includes the laying of a few urban myths, on which topic we can begin.